ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL KEMAMPUAN KOMUNIKASI MATEMATIS PADA MATERI BANGUN DATAR - Yuli Aulia Saptika; Fitri Rosdiana; Ratna Sariningsih (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
Basically every student must master mathematics taught in school because mathematics is a branch of science from various sciences but in fact many students think that mathematics is a complicated lesson that makes them feel dizzy to learn it. In the end their hearts and minds were not open to understanding mathematics when it was explained by the teacher in school so that they had a lot of problems to solve the problem and resulted in incorrect filling in the questions given. The purpose of this study is none other than to analyze students' errors in mathematical communication skills in completing flat-build material. The subjects used were students from one of the high schools in Cihampelas. This research method is qualitative descriptive and the instrument used consists of a mathematical communication ability test. Based on the results of the research, the location of the causes of errors made by students is a concept, procedure and computational error. Factors that cause errors because they do not understand simple concepts, do not know the purpose of the problem, cannot complete mathematical sentences and are not careful in calculating.